Presenting data how to communicate your message effectively - Swires-Hennessy, Ed., author (John Wiley & Sons Inc., 2014)
Presenting Data provides an easy-to-understand guide to the basic principles of data presentation and their application without the need for prior statistical training. Following the theory of each technique, poor examples are presented and analyzed, lessons drawn and principles explained and summarized along with a concluding set of good examples. A vast range of tables, charts, maps, text and data visualization are presented to illustrate errors as well as possible solutions to difficult presentational issues; throughout the book the main focus is on getting the correct message from the data. The final chapter deals with data visualization - or 'live' demonstrations of data characteristics on the internet"-- Provided by publisher. "Presenting Data provides an easy-to-understand guide to the basic principles of data presentation and their application without the need for prior statistical training.